The dynamics of Indonesia's local beauty market: an analysis of the impact of social media engagement on purchase intention - Vaharani, Amanda Andriana; Halim, Rizal Edy (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Introduction: The research aims to analyze the impact of customer engagement on brand social media on purchase intention, as well as the mediating variable of attitudes towards the brand's social media. The subjects of this study are Instagram and/or TikTok users aged 18-34 years who are familiar with and have interacted with social media content from local beauty brands on Instagram or TikTok. Methods: Data analysis was conducted using the Partial Least Squares - Structural Equation Modeling (SEM PLS) method. Finding: The results indicate that customer engagement on brand social media has a positive impact on purchase intention, which is greatly influenced by the quality of the content information presented. Brand familiarity does not have a significant influence on customer engagement. Conclusion: Furthermore, engagement on the brand's social media pages results in a positive attitude towards the brand's social media pages, which affects future purchase intentions from the brand.